Engineering of alcohol dehydrogenase 2 hybrid‐promoter architectures in Pichia pastoris to enhance recombinant protein expression on ethanol. Issue 10 (9th July 2019) - Ergün, Burcu Gündüz; Gasser, Brigitte; Mattanovich, Diethard; Çalık, Pınar
Abstract: The aim of this work is to increase recombinant protein expression in Pichia pastoris over the ethanol utilization pathway under novel‐engineered promoter variants (NEPVs) of alcohol dehydrogenase 2 promoter (P ADH2 ) through the generation of novel regulatory circuits. The NEPVs were designed by engineering of transcription factor binding sites (TFBSs) determined by in silico analyses and manual curation systematically, by(a) single‐handedly replacement of specified TFBSs with synthetic motifs for Mxr1, Cat8, and Aca1 binding, and synthetic TATA‐box integration; and, (b) nucleosome optimization . P ADH2‐Cat8‐L2 and P ADH2‐Cat8‐L1 designed by the integration of synthetic Cat8 binding sites were superior, and then P ADH2‐NucOpt . Compared to that with P ADH2 at t  = 20 hr of the fermentations, P ADH2‐Cat8‐L2 allowed the highest increase in enhanced green fluorescent protein expression as 4.8‐fold on ethanol and 3.8‐fold on methanol; and, P ADH2‐NucOpt upregulated the expression 1.5‐fold on ethanol and enhanced 3.2‐fold on methanol. Using the superior two tools, Cat8‐L2 and NucOpt, we designed P ADH2‐NucOpt‐Cat8‐L2 . With P ADH2‐NucOpt‐Cat8‐L2, the expression in the fermentation of ethanol was upregulated 3.7‐fold that is distinctly higher than that with P ADH2‐NucOpt but lower than that with P ADH2‐Cat8‐L2 ; while on methanol compared to that with P ADH2, the expression was enhanced 8.8‐fold. Extracellular recombinant human serum albumin production was also studied with P ADH2‐Cat8‐L2 and P ADH2‐NucOpt, and average recombinant human serum albumin yield (YP/X ) on ethanol was 1.13 and 0.38 mg/gWCW, respectively; whereas with P ADH2, YP/X was 0.26 mg/gWCW . We conclude that as upregulation of transcription and enhanced expression correlate with the sequence of synthetic motifs and their location in the hybrid‐promoter architectures of NEPVs in coordination with trans ‐acting factors, which are the design parameters in the engineering of binding sites; the NEPVs generated promising recombinant protein production platforms with a high impact on industrial scale production processes, as well as would open up new avenues for research in P. pastoris . Abstract : A synthetic P ADH2 library was constructed through designing ADH2 hybrid‐promoter architectures using synthetic tools, aiming to generate novel regulatory circuits to drive ethanol‐induced enhanced gene expression. Novel‐engineered promoter variants of P ADH2 were designed and constructed, by(a) replacement of native transcription factor binding site (TFBS) sequences with the synthetic tools either targeted insertion (P ADH2‐AddAdr1, P ADH2‐Aca2, P ADH2‐Cat8‐L1 ), or sequence optimization of the putative TFBSs (P ADH2‐Adr1‐L1, P ADH2‐Adr1‐L2, P ADH2‐Adr1‐L3, and P ADH2‐Cat8‐L2 );(b) nucleosome optimization (P ADH2‐NucOpt ); and, (c) being the superior tools, custom‐designed Cat8 binding‐site integration, and nucleosome optimization, were employed together in the design of P ADH2‐NucOpt‐Cat8‐L2 .